2015
DOI: 10.1038/sc.2014.240
|View full text |Cite
|
Sign up to set email alerts
|

Hyponatremia in spinal cord injury patients: new insight into differentiating between the dilution and depletion forms

Abstract: Study design: This is a retrospective study. Objectives: The objectives of this study were to present a new model for differentiating between the dilution and depletion forms of hyponatremia in patients in the postacute phase after spinal cord injury (SCI), and to identify possible etiological factors contributing to hyponatremia in these patients. Setting: University Hospital Motol, Prague, Czech Republic. Methods: Eighty-seven of 352 patients hospitalized in 2008-2012 in the Spinal Cord Unit were hyponatremi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 25 publications
0
7
0
1
Order By: Relevance
“…Therefore, we recommend regular testing und supplementation if necessary. Sodium was reduced in 24% of our population compared to the general SCI population admitted to a hospital [33] and sodium levels should be regularly tested and treated. Selenium deficiency was found in 10% and because it is supplemented without any side effects to optimize wound healing [34], no regular screening seems necessary.…”
Section: Laboratory Parametersmentioning
confidence: 89%
“…Therefore, we recommend regular testing und supplementation if necessary. Sodium was reduced in 24% of our population compared to the general SCI population admitted to a hospital [33] and sodium levels should be regularly tested and treated. Selenium deficiency was found in 10% and because it is supplemented without any side effects to optimize wound healing [34], no regular screening seems necessary.…”
Section: Laboratory Parametersmentioning
confidence: 89%
“…В частности увеличенное давление спинномозговой жидкости в комбинации с другими факторами при травме шейного отдела СМ может приводить к СНСАГ. В свою очередь острая травма шейного отдела СМ, осложнённая гипонатриемией, может обуславливать повышение давления спинномозговой жидкости [14,15]. При этом адекватная и своевременная коррекция электролитного дисбаланса является решающей при восстановлении пациентов со спинномозговой травмой [4].…”
Section: Discussionunclassified
“…The following variables were evaluated retrospectively by univariate logistic regression analysis: (1) age, (2) sex, (3) BP, (4) tracheostomy, (5) serum potassium, (6) serum chloride, (7) serum bicarbonate, (8) serum albumin, (9) intravenous intake and urine volume for 24 h, (10) haematocrit, (11) haemoglobin and the neurological assessment and radiological parameters stated above. To prevent missing potential predictors, Po0.10 was considered statistically significant in the univariate logistic regression analyses.…”
Section: Discussionmentioning
confidence: 99%
“…8 Therefore, impairment of the central nervous system may lead to either water retention, salt wasting or a combination of the two. 5,11 Previous studies have reported certain risk factors for hyponatraemia in CSCI patients, including low BP, severe paralysis, other electrolyte disturbances (serum potassium, serum chloride) and excessive water intake. 4,7 However, these factors might have many confounders.…”
Section: Introductionmentioning
confidence: 99%